Magnetic Resonance Spectroscopy of Hepatic Fat from Fundamental to Clinical Applications: An Advanced Study - Duanghathai Pasanta; Khin Thandar Htun; Jie Pan; Suchart Kothan (New Visions in Science and Technology Vol. 6, 2021)
The number of people suffering from fatty liver disease is rising around the world, sparking interest in noninvasive liver fat research. MRS (magnetic resonance spectroscopy) is a powerful tool for directly measuring metabolites in tissue or other areas of interest. MRS has been used to assess liver fat noninvasively in vivo in both research and clinical studies. In comparison to biopsy and other imaging modalities, MRS has shown excellent performance in assessing liver fat with high sensitivity and specificity. Because of these characteristics, MRS is widely used as the gold standard for noninvasive liver steatosis measurement. The goal of this book chapter is to give a quick overview of the MRS principle and its application for assessing liver fat, as well as to summarize the current state of MRS research in comparison to other techniques.